Running mechanics and gait analysis - Ferber, R.; Macdonald, S. (Human Kinetics, 2014)
Running continues 10 be the mosl popular physical activity in North America with over 50 million estimated participants. However, various epidemiological studies have estimated thai anywhere from 27% to 70% of recreational and competitive distance runners sustain an overuse running injury during any one-year period. With an estimated 16% of North Americans participating in a recreational running program (Institute 2009), approximately 27 million adults will experience a running-related injury each year, resulting in over $.35 billion in direct costs (Knowlcs 2007). Thus, health care professionals, coaches, and runners should be educated on the multifactorial nature of running injuries for the purpose of injury prevention and optimal treatment. The knee is the most common site of injury, representing 40% of all running-related injuries, and patellofemoral pain syndrome (PFPS) accounts for 46% to 62% of those injuries. Since 35% of North Americans participate in running-related activities, 48 to 62 million adults will be affected by a PFPS injury in any given year. Thus, the ability to understand the underlying factors that contribute to injuries such as PFPS is critical for prevention and developing optimal rehabilitation protocols. For an injured runner, several options are available for treatment. In many cases, clinicians perform some form of gait analysis lo better understand how the patient's underlying walking and running mechanics are related to etiology of injury. However, the multifactorial nature of any running injury demands that the clinician be well trained and understand the interrelationships between gait biomechanics, anatomical alignment, muscular strength, and muscular flexibility. Looking al any one of these factors in isolation does not adequately provide clinicians with the answers needed for optimizing the rehabilitation protocol for the patient or the information necessary for preventing injury recurrence. Therefore, this book provides an overview of the most recent research and clinical concepts related to gait and injury analysis. The book provides a more thorough understanding of the complexities of running biomechanics and the interrelationships of muscular strength, flexibility, and anatomical alignment for the purpose of providing an advanced clinical assessment of gait. Most important, the underlying theories put forth are grounded in the most current biomechanical and clinical research to provide valuable and innovative tools to improve clinical practice and the ability to rehabilitate and prevent running injuries. It references more than 250 peer-reviewed scientific manuscripts throughout the textbook and include the most up-to-date research. There is no other resource that contains a comprehensive list of running-related research. For over 10 years a team of clinical scientists, mechanical and biomedical engineers, clinicians, and biomechanists have been researching and developing novel scientific assessment techniques for running and walking injuries. The purpose of the applied research laboratory is to improve the understanding of etiology of injury and optimal treatment. However, this book is not just a discussion of this approach. Rather, the techniques and rationale for the selected variables of interest discussed throughout this book are based on this research as well as research from other laboratories around the world. Based on this approach, it is not the authors opinion provided in this textbook, that is also available as e-Book. As research continues to evolve, the authors will continue to update this book with the latest information from around the world.